Effects of nitrogen-fixing bacteria on seabuckthorn growth (Hippophae rhamnoides. L) - Mijiddorj, Ankhtuya; Lantuu, Galt; Badam, Ninj (Proceedings of the Mongolian Academy of Sciences, 2024)
Mongolia's fertilizer industry produces 2,000 tons of fertilizer in 10 years, while imports amount to 6-8 tons a year. One of the main biological features of the root system of sea buckthorn is the ability to absorb nitrogen from the air with the help of its root nodules. The main goal of the research is to identify the native nitrogen-absorbing bacteria of sea buckthorn and to increase their activity by preparing bacterial fertilizers and determining their effects on plants. In our study, we obtained 2 types of nitrogen-fixing bacteria using common microbiological methods. Sea buckthorn mongolica subspecies was used in this study. The study of root nodules of sea buckthorn (Hippophae rhamnoides L.) aims to identify symbiotic nitrogen-fixing bacteria. Sea buckthorn root nodules contain Frankia actinorrhizal microorganisms. Sea buckthorn seedlings, including those fertilized with nitrogen-fixing bacterial cultures, showed a positive correlation with plant growth. From June to September, when air temperatures are high and photosynthesis active in the field, the number of bacterial cells and nitrogenase activity were found to elevate in the root nodules of sea buckthorn plants. During this period, the roots extended 1.4 to 2.0 meters in length. The first- and second-order small roots, along with the main root, began forming small nodules filled with microorganisms. These microorganisms play a crucial role in capturing nitrogen in its molecular form from the air and converting it into a form usable by plants. However, studies on the diversity and distribution of Frankia strains have been hindered by challenges in isolating them from field-collected root nodules. In the field, nitrogenase activity in root nodules remained high from May to September, corresponding with the periods of high air temperatures and active photosynthesis.